The Importance of Posyandu in Aria Hamlet Bingkeng Village - A, Faisal; R, Rini; Fakhri, Muhammad; M, Afta; S, Egi; N, Fikri; SN, Imelda; P, Hendi; A, Rifa; H, Nissa; M, Zanet; Nofiyanti, Estin (AbdimasMu UMTAS, 2024)
Integrated service post in Indonesia known as Pos Pelayanan Terpadu (Posyandu) is a meeting place between professional services from Posyandu health workers and Posyandu's role in improving the quality of maternal and child health, Posyandu is also a center for public health information. The aim of this outreach activity to the community is to increase public knowledge and awareness about the utilization of health services at posyandu. The method used in this study is qualitative with data collection techniques through interviews, observation, and question and answer. Respondents in this study were posyandu cadres, Dusun PKK cadres, medical personnel, and the community, especially mothers with toddlers with a total of 90 participants. The results of the study show that the community's perception of the Posyandu program is quite positive, Posyandu has an important role in improving the quality of maternal and child health through the health service process, and Posyandu has become a center for public health information